TRAPPED IN THE IN-BETWEENNESS: THE NARRATION OF GENDER, SEX, AND SEXUALITY IN JEFFREY EUGENIDES’ MIDDLESEX (Universitas Pamulang, 2017)
AbstractThe 2003 Pulitzer Award’s winning novel Middlesex has been praised in the United States because it is considered to be successful in presenting new perspectives on gender through intersex character who rejects genital surgery. In addition to intersex, this novel also constructs the discourse of sexuality through incest and lesbian issue. This study is conducted to reveal how gender, sex, and sexuality are represented in the novel. Judith Butler’s concepts of gender, sex and sexuality are used in this study to understand how the author builds the discourse of incest, lesbian and intersex. In order to find out the author’s position regarding these issues, this study also aims to expose what factors have influenced the representation of gender, sex, and sexuality in the novel. The result of this study shows that this novel tends to strengthen the causality between gender, sex and sexuality by portraying lesbian and intersex as the other. Incest is depicted as something acceptable as long as it is successfully blurred the kinship and suggests consensual heterosexual relationship. While lesbian is represented as sexual deviant desire that is never accepted in the United States. Intersex which becomes the major issue of the novel is defined as an abnormality that is shameful and should be hidden. In order to be accepted in the United States, lesbian and intersex are required to transform into more coherent gender and sexuality to fulfill what Butler calls as compulsory heterosexuality. The representation of gender, sex, and sexuality in the novel are greatly influenced by the political, social, and cultural factors that developed in Greece, the United States, and Germany in the 20th up to the beginning of 21st century. Furthermore, the discourse of lesbianism and intersexuality that flourished in America when the novel was published also has an effect on the representation of lesbian and intersex in the novel. Keywords: Intersex, Lesbian, Incest, Middlesex.